SEJARAH PERKEMBANGAN TARI ZAPIN DESA MESKOM KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Sarita '; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The area is located in the traffic lane Riau International trade, facilitating contacts with various ethnic cultures. So ongoing cultural values espoused mainly dance Zapin society. This situation began to gradually causes the loss of symbols and the intrinsic meaning contained in Zapin dance. he purpose of this research is to know the background of the existence of Zapin dance Village Meskom Bengkalis District of Bengkalis, To know the meaning of Clothing used in the Dance Village Zapin Meskom Bengkalis District of Bengkalis, To know the meaning of the Movement in Dance Zapin Bengkalis District Subdistrict Village Meskom Bengkalis, To know Zapin Tari development Meskom Rural District of Bengkalis . The method used is the method Historically, data were collected through observation, interviews, kepustaka studies and documentation. In analyzing the data using qualitative descriptive. When the study began in the submission title until the completion of a revised proposal last essay writer. Results from this study indicate that the Zapin dance comes from the Arabic and then disseminated disiak and finally in Bengkalis Meskom village. Zapin dance Meskom has been progressing in accordance with people's daily life Meskom. However, fixed in accordance with the rules and norms of customary resam Malay culture itself. Plus Zapin Tari was formerly intended for the symbols of Da'wa, cheerfully invites also behave politely to anyone this is shown in every meaning of the Zapin dance movement itself. Keywords: History, Development, Dance, Zapin, Meskom